EFFECT OF ELECTRONIC CIGARETTE SMOKING ON BLOOD PRESSURE IN HYPERTENSIVE PATIENTS. EVALUATION BY NON-INVASIVE CONTINUOUS AMBULATORY BLOOD PRESSURE MEASUREMENT. (June 2018) - Crippa, G.; Bergonzi, M.; Bravi, E.; Balordi, V.; Cassi, A.
Abstract : Objective: The electronic cigarettes (EC) is a device that heats a liquid containing nicotine and flavors into an aerosol for inhalation. There is some evidence from controlled trials that electronic cigarette (EC) may help to stop smoking long-term. However, a large proportion of smokers who successfully quit cigarette smoking continue to use EC for unlimited time, switching from an addiction to another. There is a clear similarity between the detrimental vascular effects of EC and conventional cigarette. Little is known about the acute influence on blood pressure (BP) of nicotine inhalation by EC and it's duration of action in hypertensive subjects. Aim of this study was to evaluate the magnitude and time-course of BP changes during EC smoking. Design and method: This is a randomized, cross-over and placebo controlled study. We evaluated 30 mild-to-moderate hypertensive patients on pharmacological treatment and adequate BP control (< 140/90 mmHg). Patients (22 males, mean age 54 ± 21 years) were former smokers, who quitted tobacco cigarette in favor of EC at least 6 months before. BP and heart rate (HR) were measured by continuous non-invasive ambulatory BP and ECG monitoring (SOMNOtouch NIBP). BP and HR were monitored during a 30 minute rest in the sitting position; during other 30 minutes after smoking EC (inhalation equivalent to 0.8 mg of nicotine of a regular cigarette) or placebo EC (same device, same flavor but no nicotine in the solution). Results: EC vaping was accompanied by significant increase blood pressure, which lasted about 30 minutes (average 28 ± 11 minutes). Compared to placebo the EC smoking increased systolic BP by 9, 6 ± 4, 1 mmHg, diastolic BP by 7.1 ± 3.9 mmHg and heart rate by 16, 4 ± 13 beat per minute. All the differences resulted statistically significant (Student's t test P < 0.05). Conclusions: Under these experimental conditions, EC smoking caused a statistically significant increase in BP and HR in hypertensive patients. This effect seems also clinically relevant since the duration of BP increase was relatively long (28 minutes) and the daily number of inhalations, in EC smokers, is usually high (> 20).